PROAMBIENTE dans la région du “Bico do papagaio” – contributions principales - Clara Soler Jacq; Neli Aparecida de Mello-Théry (Confins)
The objective of this article was to analyze the main contributions of the Program for Social and environmental Development for the Rural Family Production in the Amazon - PROAMBIENTE in the region of “Bico do Papagaio”, in the north of Tocantins. The first questions that guided the research were: Being a short-term program, was there any step towards the agroecological transition in the region, as planned in 2005? What contributions did it bring to the families that participated to it? For this purpose, secondary data was consulted, and primary data was collected through fieldwork conducted in June and July 2017. In general, the conclusions of the article are: 1) the program has given greater awareness to the families about the control of the use of fire, 2) there was an increase in fruit production in the region and agroforestry yards and 3) the change in land use that the families had planned in 2005 occurred.